Pendampingan Konversi Sampah Menjadi Bernilai Investasi Dengan Menggunakan Aplikasi Berbasis Android di Desa Sumber Gedang Pandaan Pasuruan - Abdillah Mundir; Akhmad Alifan; Ummi Aminatuz Zuhriyah; Durrotul Ilmiyah; Titin Musarofa; Syaiyidatun Nadzifa (LPPM Universitas Yudharta Pasuruan, 2021)
Garbage is an object/residual substance that is not used from human life, and should receive serious attention and handling. However, due to a lack of public understanding, this waste problem has been neglected, as is the case in Sumber Gedang Village, Pandaan District - Pasuruan. One of the existing solutions from the Yudharta University student service group is to empower youth through the movement to convert waste into investment value by initiating an Android-based waste bank. Through the ABCD approach, the results of this service can contribute and make changes in waste management which so far have not been in accordance with environmentally sound waste management methods and techniques. In addition, this service has also changed the waste management system from burning to an integrated waste management system by sorting according to the category, so that it has a selling value and contributes to the social economy of the community